2020
DOI: 10.1021/acssensors.0c01441
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Suppression of Physisorbed-Water-Caused Hysteresis in Graphene FET Sensors

Abstract: Hysteresis is a problem in field-effect transistors (FETs) often caused by defects and charge traps inside a gate isolating (e.g., SiO 2 ) layer. This work shows that graphene-based FETs also exhibit hysteresis due to water physisorbed on top of graphene determined by the relative humidity level, which naturally happens in biosensors and ambient operating sensors. The hysteresis effect is explained by trapping of electrons by physisorbed water, and it is shown that this hysteresis can be suppressed using short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
(65 reference statements)
0
13
0
Order By: Relevance
“…The possible reason of the V Dirac shift is due to the interaction between the device and the ions in PBS solution, and the Dirac point shifts of the GO/Gr FET and Gr FET are comparable with the previous reports and acceptable in real applications [ 53 ]. To further confirm the stability of the GO/Gr and Gr FETs, we performed the hysteresis test since the Gr FET normally exhibits hysteresis due to water absorption on the channel surface when it works as biosensors [ 54 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The possible reason of the V Dirac shift is due to the interaction between the device and the ions in PBS solution, and the Dirac point shifts of the GO/Gr FET and Gr FET are comparable with the previous reports and acceptable in real applications [ 53 ]. To further confirm the stability of the GO/Gr and Gr FETs, we performed the hysteresis test since the Gr FET normally exhibits hysteresis due to water absorption on the channel surface when it works as biosensors [ 54 ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This can cause uncertainty in evaluating the doping level of graphene and the subsequent amount of detected molecules. 51 , 52 To test the stability of Gr-FET devices, we monitored the channel resistance of our samples every week (in air) under ambient lab conditions (humidity < 30%). As shown in Figure 4 f, a very small change in resistance was observed over a period of 6 weeks which demonstrates the stability of our devices.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Bartošík et al found that the p-doping of graphene FET sensors is caused by the capture of graphene due to the chemical adsorption of water on the graphene–SiO 2 interface [ 37 ]. As shown in Figure 3 a, when water molecules are physically adsorbed on the graphene surface at higher relative humidity (RH%), the water molecules are captured by graphene due to chemical adsorption on the graphene–SiO 2 interface.…”
Section: Sensing Principlementioning
confidence: 99%
“… ( a ) Schematic diagram of the initial state of a graphene FET after physical interaction of electrons with water; ( b ) electrons change immediately after the gate voltage is applied; ( c , d ) schematic diagram of the state when a more extended grid voltage is applied ( c ) at lower and ( d ) at higher relative humidity [ 37 ]. Copyright (2020), used with permission from Elsevier.…”
Section: Figurementioning
confidence: 99%